2020
DOI: 10.1115/1.4049121
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Description of Flow-Deck Interaction in Consecutive Green Water Events

Abstract: This paper gives a detailed description of the main hydrodynamic characteristics of different types of green water events occurring on a fixed structure in a series of experiments. High-speed video, at 250 fps, was used to capture the flow details from regular waves produced inside a wave flume. The green water events were classified according to their type and the results of the evaluation from the apparent and effective interaction features. The air cavities in the PDB (Plunging Dam Break) type events were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…Yao and Hu [28] explained that some phenomena could have triplevalued water surface amplitudes, such as the air trapped beneath an overturning plunger. Furthermore, the snapshots presented in [9,12] clearly show that the initial stages of some shipping water events have these features. Recently, Hernández-Fontes et al [29] introduced the concept of multiple-valued water surface (MVWS) elevations to refer to the amplitudes of the several water surfaces that can be measured at a specific location, along a horizontal domain, in some 2D hydrodynamic experiments, as illustrated in Figure 1b.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Yao and Hu [28] explained that some phenomena could have triplevalued water surface amplitudes, such as the air trapped beneath an overturning plunger. Furthermore, the snapshots presented in [9,12] clearly show that the initial stages of some shipping water events have these features. Recently, Hernández-Fontes et al [29] introduced the concept of multiple-valued water surface (MVWS) elevations to refer to the amplitudes of the several water surfaces that can be measured at a specific location, along a horizontal domain, in some 2D hydrodynamic experiments, as illustrated in Figure 1b.…”
Section: Introductionmentioning
confidence: 88%
“…In ocean engineering research, experimental observations have suggested various patterns used to characterize different types of green water. Broken flow features are often seen, if they are generated by breaking waves [5][6][7][8], or air cavity formation at the start of the deck, if the incident waves are unbroken or partially broken [9][10][11][12][13][14]. In 2007, a classification of different types of green water was suggested by [9], who described the different events found in regular wave trains: The dam-break (DB), the plunging-dambreak (PDB), and the hammer-fist (HF) types.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations